Treadmilling by FtsZ Filaments Drives Peptidoglycan Synthesis and Bacterial Cell Division - Bisson Filho, Alexandre W. (Science, 2017)
The mechanism by which bacteria divide is not well understood. Cell division is mediated by filaments of FtsZ and FtsA (FtsAZ) that recruit septal peptidoglycan synthesizing enzymes to the division site. To understand how these components coordinate to divide cells, we visualized their movements relative to the dynamics of cell wall synthesis during cytokinesis. We found that the division septum was built at discrete sites that moved around the division plane. FtsAZ filaments treadmilled circumferentially around the division ring, driving the motions of the peptidoglycan synthesizing enzymes. The FtsZ treadmilling rate controlled both the rate of peptidoglycan synthesis and cell division. Thus, FtsZ treadmilling guides the progressive insertion of new cell wall, building increasingly smaller concentric rings of peptidoglycan to divide the cell.